The Lowe syndrome protein OCRL1 is required for endocytosis in the zebrafish pronephric tubule. - Francesca Oltrabella; Grzegorz Pietka; Irene Barinaga-Rementeria Ramirez; Aleksandr Mironov; Toby Starborg; Iain A Drummond; Katherine A Hinchliffe; Martin Lowe (PLoS Genetics)
Lowe syndrome and Dent-2 disease are caused by mutation of the inositol 5-phosphatase OCRL1. Despite our increased understanding of the cellular functions of OCRL1, the underlying basis for the renal tubulopathy seen in both human disorders, of which a hallmark is low molecular weight proteinuria, is currently unknown. Here, we show that deficiency in OCRL1 causes a defect in endocytosis in the zebrafish pronephric tubule, a model for the mammalian renal tubule. This coincides with a reduction in levels of the scavenger receptor megalin and its accumulation in endocytic compartments, consistent with reduced recycling within the endocytic pathway. We also observe reduced numbers of early endocytic compartments and enlarged vacuolar endosomes in the sub-apical region of pronephric cells. Cell polarity within the pronephric tubule is unaffected in mutant embryos. The OCRL1-deficient embryos exhibit a mild ciliogenesis defect, but this cannot account for the observed impairment of endocytosis. Catalytic activity of OCRL1 is required for renal tubular endocytosis and the endocytic defect can be rescued by suppression of PIP5K. These results indicate for the first time that OCRL1 is required for endocytic trafficking in vivo, and strongly support the hypothesis that endocytic defects are responsible for the renal tubulopathy in Lowe syndrome and Dent-2 disease. Moreover, our results reveal PIP5K as a potential therapeutic target for Lowe syndrome and Dent-2 disease.